Modern trends in global urbanization process and the role of migration - Mostova, Iryna (Human Geography Journal, 2014)
The influence of international population movements on the scale of global urbanization is analyzed in the article. The state of contemporary migration in the world is carried out. Dynamics of the world’s urban population is shown. The largest cities of the world and the major migration corridors are represented. Past and current state of the global processes of urbanization in the context of developed countries and developing ones is under consideration. Correlation analysis between urbanization of a particular territory and the proportion of immigrants among the total population is done. The substance of the concepts «slums» and «global cities» is explained.